2011
DOI: 10.2136/sssaj2010.0409
|View full text |Cite
|
Sign up to set email alerts
|

Hemlock Infestation and Mortality: Impacts on Nutrient Pools and Cycling in Appalachian Forests

Abstract: E astern hemlock is a major component of riparian forests in the southern Appalachian Mountains (Narayanaraj et al., 2010). As the dominant conifer in riparian areas, this species plays an important role in regulating nutrient cycling processes and climatic conditions in both terrestrial and aquatic environments (Ellison et al., 2005). Th e hemlock woolly adelgid (Homoptera: Adelgidae), an exotic pest, was introduced to the mid-Atlantic region of North America from Asia in the 1950s and has spread throughout m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 39 publications
4
31
1
Order By: Relevance
“…This prediction was supported most clearly for changes in litterfall, which is one index of aboveground primary productivity [98]. In the girdled treatment plots at HF-HeRE, there was a sharp pulse in litterfall followed by a gradual decline [19]; similar patterns have been observed in other hemlock girdling experiments [22,39,99]. This shift reflects only the transient loss of standing biomass as the canopy died; litterfall recovered within four years to premanipulation (i.e., control-plot) levels as understory shrubs (primarily Rubus spp.)…”
Section: Ecosystem Dynamicssupporting
confidence: 73%
See 1 more Smart Citation
“…This prediction was supported most clearly for changes in litterfall, which is one index of aboveground primary productivity [98]. In the girdled treatment plots at HF-HeRE, there was a sharp pulse in litterfall followed by a gradual decline [19]; similar patterns have been observed in other hemlock girdling experiments [22,39,99]. This shift reflects only the transient loss of standing biomass as the canopy died; litterfall recovered within four years to premanipulation (i.e., control-plot) levels as understory shrubs (primarily Rubus spp.)…”
Section: Ecosystem Dynamicssupporting
confidence: 73%
“…Tsuga canadensis has little, if any, resistance to the hemlock woolly adelgid [34] and rarely recovers from chronic infestations [35,36]. In many infested stands, >90% of T. canadensis dies within 10 years of the arrival of the adelgid [37][38][39].…”
Section: A Natural Experimentsmentioning
confidence: 99%
“…This result is consistent with that of Jenkins et al (1999), who found no significant changes in C pools ;3 years following hemlock infestation at sites throughout southern New England. Knoepp et al (2011) also found no significant loss of soil C content 4-years following hemlock loss at the Coweeta Long Term Ecological Research. Hence, the initial impacts on the C cycle appear to be limited to a transfer of C into woody debris.…”
Section: Discussionmentioning
confidence: 81%
“…The hemlock woolly adelgid ( Adelges tsugae Annand), an invasive insect from Japan that in North America feeds exclusively on eastern hemlock and its southeastern (USA) endemic congener, Carolina hemlock ( T. caroliniana Engelmann), is moving rapidly both southward and northward (Fitzpatrick et al, 2012), killing >90% of hemlocks it encounters (Orwig, Foster & Mausel, 2002; Eschtruth et al, 2006; Knoepp et al, 2011). Hemlock has little resistance to the adelgid (Ingwell & Preisser, 2011) and as yet has shown no recovery from chronic infestations (McClure, 1995; Orwig et al, 2012).…”
Section: Introductionmentioning
confidence: 99%